(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Unity of Architecture The Avery Library at Columbia University, NYC, is too cold for whoever comes from Rome. “Air conditioning, while it makes us comfortable anywhere – wrote Daniel Solomon – obliterates the time of day, the weather, the season, and the distinctiveness of the places of the world.” It is one of Daniel’s few claims with which I agree only in part. Air conditioning in the States always reminds you of that American distinctiveness of those five, six, or even ten degrees centigrade below human well being which the thermostat is obstinately maintained wherever the Star and Stripes is raised aloft, forcing you to feel uncomfortable anywhere, from Chicago to Miami, from Hawaii to Puerto Rico, passing through San Francisco and New York, in fact. But the Avery Library is one of those places where I love to linger a long while, without any clear aim, moving among its files of shelves to slowly harvest book after book, with that apparent volubility with which, in China, the women harvesters – large trousers and wide sunhats – walk among the rows of Camellia Sinensis, here and there picking of the very first precious tea leaves, immediately dropping them – as if gold coins – into the bag hanging from their belt. Once concluded my small harvest of books, I then love to go down and leaf through them in the twilight of the lower floor of the Library where it is even colder, but peace more absolute. I choose my seat at the back of the room, facing the entrance. It is a pragmatic choice; on the left the door opens to a small photography room, where you can reproduce with the camera – today with a mobile phone –the most precious pages of your harvest. On the right, closer to the entrance, sits Ms. Librarian, very polite, whose courtesy tries to clothe strict American severity with good English cloth. It was July then and she was wearing a summer dress. For me wearing a sweater under my jacket and all the buttons fastened wasn’t enough. I was cold. But I had to resist, convinced then, as I am now, that this is most certainly the test you must undergo in the States, to prove that yourself are worthy of their standard of civilization. While reaping my small pile of books I was accompanied by a young Italian student who had completed her PhD thesis for La Sapienza at Columbia University. While I was settling at the table in the cold reading room, she had lingered a little longer among the shelves to glean some other texts; she soon joined me in the reading room, hurriedly on tiptoe. With an almost triumphant smile, she added a book of her choice entitled Global City Blues to my small stack. Nice title, I whispered quietly as I noticed the author’s name: Daniel Solomon, still unknown to me. I thought that the young PhD wanted to bring that book to my attention because of the word “Blues”. She was well aware of my passion for the twelve lines, the blue notes and all the rest, which I had cultivated since sixty years earlier – then, truly a child - General Clark’s Fifth Army had appeared in Rome freeing us from the remains of General von Mackensen’s Fourteenth. With the Americans, the New World suddenly arrived here in Rome with its hurried manners, with its unprecedented modernity, its music and, with it, the Blues. The real Blues I mean, not only the one that endorses Glenn Miller’s boogies, but the deep and naive Blues that the black soldiers strummed on badly tuned guitars while leaning on their Jeeps parked in the street, waiting for the white graduates to come out of the Command and order to be taken elsewhere. And my mother, a musician who studied Folk music, responded to my precocious fixation for that repetitive round of notes by teaching me in detail the Blues scale and the most classic riffs. But I was entirely mistaken; Daniel Solomon’s book had not been chosen to please my passion for the Blues. This book is about Wu, the young student told me in a very low voice: it is about Professor Wu Lianyong. Professor Wu Liangyong in those early years of the new century was already the great old man of modern Chinese architecture, a Beijing school. He was already over eighty. You perceived his immanent presence as soon as a Chinese colleague, pronouncing his name to introduce the history of the faculty of architecture at Tsinghua University to you, instinctively turns his eyes towards the top of the grand staircase that leads to the upper floors from the atrium of that famous school where the reproductions of a Greek Order and the Chinese Order face each other. The founder-professor, thus, still dwelt on his Mount Olympus, so near to us mortals. At that time no one in Italy knew professor and architect Wu Liangyong. Not one history of contemporary architecture bore his name or published his works. Not one magazine article had ever been dedicated to him. In truth, modern Chinese architecture and the contemporary Chinese city were essentially ignored even by our historians who kept most abreast. The abstract elegance of Ieoh Ming Pei, a consonant tribute to Western modernity, seemed to have established the path that Chinese architects would have had to follow to enter the history of contemporary architecture. A path that would have been difficult to follow with conviction even by us Italian architects. I had enrolled in the Faculty of Architecture in Rome almost fifty years before the discovery of Daniel Solomon’s Blues. I was eighteen. I learned with mouth agape, the America of the soaring skyscrapers, Hollywood films, speed, the line of the 1954 Studebaker Commander; this is modernity, I said to myself, the only one that can make us young people feel alive. In my high school (Liceo Classico) books on the history of Italian and European art, I had looked for something that resembled that primordial vigor. Modern architecture, in those school books, was treated as an appendix added to the text to justify a new edition. Only one pen drawing, in black and white, by Erich Mendelsohn – the Shocken Warehouses – reproduced as a small image, seemed to me to have something of that vital impulse. I began redrawing it with my fountain pen and reinventing it every day, ignoring all I had learned, in the last three years of high school, from those massive volumes of Italian and European art history; enthusiastic, unsuspecting pilgrim on his way to Ieoh Ming Pei. But, that the same period, leafing through another ponderous art book, discovered gleaning in my spare time in my mother’s library – she was passionate about music and theater – I was attracted to the perspective reconstructions of the “vedute per angolo” by Ferdinando Galli da Bibbiena (1657-1743). Ah – I said to myself – here are the secret physical laws that are hidden behind the spectacular scenes of classical and baroque theater, rhetorical and musical; this is what induces in us, unaware spectators, the illusion and perceptive emotion that makes us adhere even sentimentally to a place, whether imaginary or real, even when built repeating the most classic and “old” architectural motifs. “So – I said to myself – the great architecture of the old cities, of their dusty monuments, so far from the vital vibrations of modernity, is only the ceremonial dress of a very modern intellectual device, made of absolute and variable geometries, of mathematical relationships still incomprehensible to me, of flights towards different infinities – right, left, above, even below – that branch off from objects that appear stolidly traditional, almost stale in their centuries-old repetition of ancient symbols …”. “No, please, seek your father’s advice on how to build a house in this beautiful village.” Is how my mother addressed the son of the farmer who had hosted us ten years earlier in Arquata del Tronto, the first summer of 1943 - the war had now come to Italy – while we were spending a semblance of vacation that was, instead, an escape to the countryside, where perhaps something to eat could be found. And where, above all, there was no danger of bombings. Arquata is a village dominated by the ruins of a medieval castle and overlooking the still narrow valley of the Tronto river that rushes from the Sibyllin mountains of the Apennines towards the Adriatic Sea. The young man was starting to build the house for his coming marriage; soon. He was very young, he wanted to get married before leaving for the front. With a group of friends he had begun to trace the foundations. I don’t know how my mother perceived the young man’s inexperience. Perhaps the materials chosen for the occasion – autarchic and cheap materials of modernity - perhaps the shape of the plan, perhaps the fact that it was built isolated on the lawn in front of his parents’ house. I do not know. But I asked her. She told me something about modernity that makes you lose the rules of living; therefore of building. I didn’t understand. She could tell. From that day, on walks through the village or on short visits to homes to buy some milk or bread just out of the oven, she never failed to point out to me the materials with which the houses were built, the spontaneous, but constant, order of the doors and windows, the very few variations of the external and internal stairs and the shape of the kitchen around which the whole house arranged the other rooms. When we went to the fields uphill of the village, she showed me the profile of the distant settlements, the color of those clumps of ancient walls so like the other colors of the landscape. And finally, of course, she spoke to me about the great Sibyl, the goddess who once – even before the ancient Romans! – lived on the highest mountain and – who knows – maybe still lived there if the girls of a valley next to ours once a year join in an ancient dance to honor Her. My cousin Giuseppe was 10 years older than me. Born in Catania, Sicily, he graduated in Engineering from the Turin Polytechnic; became one of the very first nuclear engineers in my country. While attending his Master of Science in Nuclear Engineering in Latina, not far from the capital, in a course held somewhat in secret by the US, he was often our guest in Rome. With him I talked about my future with more freedom than with my parents. I was still unsure: Medicine? Physics? ... Architecture? I spoke to him about architecture with passion, but expressing my deep disorientation. No, I didn’t want to choose to be disoriented for life. Oh yes, architecture was beautiful, but it induced conflicting impulses, confusion, like being in love with three girls at the same time ... Cousin Giuseppe saw my naive modernist drawings, he let me talk about Bibbiena and the ancient villages, my questions on “the art of living” as my mother used to say. Of modernity and tradition (those days I used to say “old architecture”). Then I talked to him about Physics, of which I knew nothing, but seemed to me emanating the certainty of the search for truth; then of Medicine, which sought the truth in man to help him live, to survive. Two professions that seemed to me then without shadows, indeed even ennobled by a humanitarian purpose: the progress of science and the care of others. Which of path to choose: Physics or Medicine? I asked a new scientist of the most modern of the sciences of the time. You have to enroll in Architecture, he replied. Now you are like a library bookshelf where you have begun to place, side by side, books about the city and the men who live in it, books that seem to be in irremediable contrast with each other, whose mere sight creates disorientation. But it is precisely by transforming ourselves into a library in which everything – meaning all ideas - can communicate with everything – he meant with all ideas –, even with its own opposite, we can hope to contribute to the progress of science, of ... philosophy ... of cities ... of architecture. Dear me. He certainly spoke with words acquired in the most exclusive Master of Science school in Italy. After a few more days of conversations I told him that I had decided: I will enroll in Architecture. “Then remember”, he told me, “don’t follow the latest fashion. Keep to one side, put your entire internal library between you and fashion”. I didn’t quite understand, but I liked that very much. That evening, at the end of the dinner, in the presence of my cousin Giuseppe – my sponsor – I communicated my decision to my parents. “Oh God!” said my father, a humanities professor from a family of humanities or science professors. And he looked at my mother who did not return his alarmed look, but smiled as she was peeling an apple with a fork and knife, as for her didactic and formal etiquette. Formal etiquette was not contemplated in the style with which architecture professors, in my day, treated freshmen and, in general, first-year students. Relentless submission to work, learning architecture through the reconstruction, from life or from documents, of all the styles of the past and, above all, of the great architectural nodes of each style. Inflexible affirmation of the architect’s profession as that of a very difficult craftsmanship, professed using every ancient tool with mastery. There were no modern tools yet. At least not in our school. In the upper three years, then, the tone of many professors was that of military authority which, in the case of the most cultured among them, assumed the tone – I believe – of medieval universities; theological absolutes of assumptions and, at the same time, Erasmian subversion of the students tolerated neglectedly by the teachers, only to be repressed publicly by the same teachers, if they had the time and the will. Modernity, modernity without adjectives, where was it to be found? It meandered only among us students and became synonymous with freedom. Ow! In spite of everything, during that authoritarian training in which very few teachers, mostly young, seemed to ambiguously want to initiate a dialogue with us young modernists-by-youth, I learned a lot. Above all, I learned that my initial radical contradictions between primordial modernity, the mirage of meta-historical compositional rules and the enchantment of natural living – which seemed to eliminate the need of the architect’s existence at the root – in an Italian school of architecture would not have found the clear answer I was looking for in favor of one or the other. Especially in the school of Rome, where those contradictions, along with so many others I didn’t even suspect at first, seemed to be resolved by all coexisting in a unitary, necessary multitude in the great flow of history. My class, like the previous two or three, in the fourth year course encountered a professor who wanted to be decisive. Decisive and oppositional. Opposed not only to the teaching methods of the faculty, authoritarian but, ultimately, lax; oppositional above all and more precisely with respect to the unitary multitude of contradictions that, despite our modernist aspirations, we had begun to recognize in the identity of architecture. That professor was Saverio Muratori, who recently obtained the chair of Architectural Composition, in 1955. Modernity, tradition, language, technology, history – its flow, I mean, which renders every truth relative – everything in its course was used as an essential, but an ancillary, prop to research, that is, placed outside the scene that it helped to build, or rather: outside the framework of the aims of its research. Which wanted to be a scientific research on the laws of constructing man’s dwelling on the planet: in the enormous and different natural and climatic spaces, in the differently opportunistic agricultural colonizations, in the villages of different materiality and culture and – finally and to begin with – in the city. Regardless of the period. That is, of history. And the city of Rome, the city par excellence, for him who came from a Po Valley family tradition – remember the Gauls? And the Lombards? And the medieval autonomous communes? – had been embraced with passion and chosen as the privileged field of research from which, with the greatest possible clarity, through the most intact and numerous examples of the highest form of construction, to extract the laws that govern man acting in giving form – or rather: in giving language to his own da-sein, to his own being, on the planet. It was as if Rome, finally and in a literally master-ful manner, could provide the supreme subject of investigation for his research – begun years earlier in a Rome, Byzantine and medieval, of the outskirts: Venice – and, at the same time, represented proof that yes, indeed grammars and constructive principles of each culture possesses a common deep structure and common formative principles. Years later, we young modernists could have recognized in Saverio Muratori’s research the same inspirational motives as Noam Chomsky’s Generative Grammar. But at that time – at the very end of the 1950s – in Italy nothing was known about Chomsky, even though, in 1957, he had just written his first major essay, Syntactic Structures. Oh, yes; when Chomsky’s thought reached even us still young Italian architects – we were interested in his political positions more than in his scientific achievements – it really seemed to me that I held in my hands proof of what we had intuited in Saverio Muratori’s research; it being a research similar to that of an entomologist who investigates winged hymenoptera’s innate ways of building their habitat, we take bees, in their variants of species and environment - that is, of culture and context, coming back to the case of humans. Indeed: perhaps, was it not Chomsky who openly established that language, that is the highest expression of identity of each human civilizations dispersed throughout history and geography, was nothing more than an adaptive, contingent, therefore historical, variant of the innate and permanent linguistic structure of an animal species, ours? And basically, did not Saverio Muratori try to demonstrate that what we call architecture in all its linguistic variants, in all its thematic and formal, environmental richness, is never the result of innovative decisions, but only of obligatory choices in a repertoire, albeit vast, in any case limited because given as innate and admitted as possible by our very nature? Architecture not as a creative act, not as an always renewed decision of thought, but as destiny. Ow! We discussed this, in different words, after each lesson with Professor Muratori. And we young modernists, who, in order to live with the idea of architecture as a unitary multitude of contradictions, had transfigured modernity into freedom, did not want to surrender to the idea of architecture as a preordained destiny. After having audaciously attended Professor Muratori’s lessons and having learned to perfection – and out of spite – the classification tables of the birth and development of dwelling types and morphological aggregations of the human habitat and having finally designed a-functional spatial modules – almost original cavities available for every primordial need – elementary housing types, preordained aggregations of houses and small services, modular workspaces and – here we are! Full circle –large monumental spaces that adapted their shape since the Pantheon and the great karst caves, we rebelled. We threw overboard both the course and Professor Muratori’s dominance n the school. But the consciousness of architecture as a destiny of the species dove into the depths of our conscience as nascent architects, without dissolving. Without telling ourselves, we well knew that in the ancient dialectic between freedom and destiny, freedom could truly win if fate yielded to human will. But, as the ancients teach us, fate does not even bend to the will of the gods. Thus, our will as designers who, chasing the flight of those we elect as the “stars” of architecture, would like to always have the revolutionary force of a dramatic overwhelming love to realize fully, in the freedom of invention, our identity as architects, in reality it is nonetheless a will of the species that remains in the space of its destiny. For this reason, the experience, not without its drama, we had during Professor Muratori’s course, instead of defeating the idea of architecture as a unitary, necessary, multitude of contradictions resolved in the great flow of history, perfected it. In the space of the destiny of the species, the contradictions are only apparent, all being only those that can be contemplated by our primal nature. And it seemed to me that the difficulty of being “modern” that transpires from the recent history of Italian architecture was not a symptom of backwardness, but of a conscious – more often than not, unconscious – resistance with respect to the illusion of considering history as a sequence of acts of rupture, denial – condemnation – overcoming of every recent past, the one from which every generation originates. Thus, in my early academic youth, I read and reread in this framework the recent history of Italian architecture, bombarding it with questions to obtain confirmation: perhaps Italians between the two wars did not make of Futurism – so verbal and gestural and theatrical and moving with Antonio Sant’Elia’s fate – the screen behind which to defend oneself from the desperate Germanic functionalism which refused by now – after the defeat in the Great War – any relationship with history? And in those decades, did not Italian architects use all the possible idioms of their culture – made up of deep and ancient diversities – to re-establish in any case continuity with the architectural research interrupted by the First World War, among which, in fact, was Futurism itself? And had Terragni – and Libera with him – not wanted to understand modernity essentially as a decisive formal experience in history - always, therefore, maintaining himself free to let his own pencil and his own thoughts flow within all the symbolic forms of classicism – from Michelangelo to the twentieth century – and of modernity –from Futurism, to Expressionism, to the a-functional construction and deconstruction of space all the way to the sublime interpretation of the modern city as a pure symbolic form synthesized in the mysterious architectural lump of the Frigerio building? And how often did the Italians seek any “external” support for their linguistic convictions to support their position with respect to the modern world? After the Second World War, in fact, in the years of my first training, the official Italian architectural culture perhaps did it not continue in its effort to avoid the “international style” – now victorious – taking the path of neo-realism, as if this were really imposed by the particular backward conditions of the popular masses of modern Rome and of our South? and the linguistic and cultural revival of Neo-Liberty, was it not attributed to the needs of stability and identity of the industrial bourgeoisie of the North West? And did not the hyper-castellan image of the Velasca Tower revive the medievalist tradition of the 19th-century Kingdom of Lombardy-Venetia School of Architecture? And didn’t Aldo Rossi’s “reactionary” language affirm, therefore, the relevance of Lombard neoclassicism that all of us Italians had learned, as schoolchildren, from Giuseppe Parini’s eighteenth-century poems? And finally: Carlo Scarpa’s experience – Byzantine in the preciousness of gold, glass and humble materials made exquisite by his drawings – did he not perhaps use Frank Lloyd Wright’s polilingualism as a passport to be welcomed into the realm of modernity without passing through the customs of the “international style” or even worse that of the more austere late Central European functionalism? In order to broaden my polytheistic workout of questions, as the turn of the century approached, I began to visit the United States quite systematically, following, of course, Zevi and Giedon’s “American” lesson of, but above all go back upstream, along the American current that many years earlier had reached us Italians, surprising us with the emergence of Louis Kahn; an apparition that seemed to me to explode the concept of modernity in the very country that had produced the 1954 Studebaker Commander and which also dismayed Bruno Zevi, the American, somewhat. It was the opening of a window on an American landscape unknown to us that I have since promised myself to explore live when commitments allowed me. Piacentini, in the period of his undisputed domination, by virtue of his international experience, had, by carefully selecting them according to his judgment and his intentions, made the currents and the leaders of American modernity known to the Italian architects – very provincial for the most part. So in his 1930 book, Architettura d’oggi (Architecture today), he made no mention of the school of Philadelphia, relegating the name of Paul Cret only to a snippet in the caption of a photo of the iron pylon of the Benjamin Franklin bridge almost to prevent someone from realizing how crucial the knowledge of the Franco-American master’s institutional works were in the development of his own grand and institutional language. Nor did Bruno Zevi, in his Storia dell’architettura contemporanea (History of Contemporary Architecture), mention the Philadelphia school and Paul Cret. The Philadelphia school, I told myself, is a place to investigate personally. At the same time, I began my systematic visits to China with increasing frequency. It was inevitable, therefore, that the Philadelphia school would become even more the center of my attention. From my travels in China, I understood that not only Kahn’s linguistic roots radiate from it, but also Liang Sicheng’s cultural roots, the assertor of the need for modern Chinese architecture to find its language and its reason in the study of architecture, city, landscape of historical China. Thus was the reason of my startled response in the hall of the Tsinghua University School of Architecture in Beijing: Wu, Professor Wu Liangyong, Liang Sicheng’s most important student, was still a living presence in the faculty he himself, when a young man, had founded on his teacher’s mandate in 1946, starting the three-year Bachelor’s program. A year after that revelation, Professor Wu unexpectedly descended among us mortals during a subsequent trip of mine to Beijing and I was able to get to know him personally. I had created an international design workshop for my School in Rome to be held in the Tsinghua School of Architecture in Beijing. Not unintentionally I had asked for Laurie Olin’s collaboration, landscape architect from Philadelphia, professor of landscape at the University of Pennsylvania, academic heir to Ian McHarg. In Beijing, certainly not by chance, he had been called to found and launch, as the first director, the Department of Landscape, demanded by Professor Wu. The workshop was a challenging act of founding stable academic relationships that still endure. While the workshop was almost concluded, a small old man with a very young face, almost childlike to us Europeans, suddenly appeared in the large classroom where we were working, accompanied by a young faculty professor. He passed between the tables, always speaking in Chinese with his companion, stopping with interest, now here, now there, to observe the drawings on which the groups of students, Italian and Chinese, were laboring, and then disappeared as he had appeared, without another word. Sitting at my table in a corner of the large classroom I followed the scene as you follow the rapid hover and go of a bee from one chalice to another. It was Professor Wu, the young Chinese teacher whispered back to us. The next day we exhibited all the drawings elaborated in the workshop on the walls of the great hall. Almost the entire faculty of the School came. In the front row Professor Wu. As soon as we Italian teachers finished the introduction to the work, Wu stood up and, turning to his Faculty, he himself continued the presentation of our work speaking in English, describing each table in detail and overall, extracting qualities that, in my opinion, were barely hinted at in the drawings and sliding over, however, on the childishness and clumsy movements of student projects. The linguistic polytheism of us Italians in that experience was rashly enriched with assonance with the place and its history, both on the scale of the landscape and architecture, trying to merge them into a design act. Of this clear attempt he derived the greatest value of that didactic experiment. The applause was for him. By extension, for us too. I clapped loudly. A long friendship had begun, almost defined by the rules governing the relationship between student and teacher. A strong friendship, stable over time, based on growing harmonic consonances and my desire to learn, to understand. For this reason, in the icy shadow of the Avery Library I immersed myself in the pages of Daniel Solomon’s book and, guided by Wu’s name, I read and reread all of Daniel Solomon’s Blues Licks dedicated to Wu Liangyong, those short and fulmineous, those almost as long as a whole chapter. I rose when finished and in the tiny photography room, helped by the young scholar, I photographed all the pages of Solomon’s book dedicated to Wu. “A perfect synthesis, I told myself, I could have written it myself”. I wished I had written it myself. Who is this Solomon? Meet him, I noted in my memory. I continued reading Solomon’s great Blues on the return trip. I did not forget it when, years later, I met Daniel Solomon in Rome. In Rome, when I met Daniel Solomon, an ancient friendship began, I must confess, as of those who, separated by life’s fortunes, unexpectedly find themselves together, with so many things to speak of, and the certainty of being understood by the other by the fact of coming from a distant and still present common root. It was not so, of course – geography, fortunes, languages, beliefs have separated his elders and mine for millennia – but it is as if it were. Even the docking on the beach where lives the ideal goodness – or rather the goddess – of the historical continuity of architecture – or rather, of the human habitat – took place in different ways, across different seas and different storms. And yet, when we talk about architecture I always feel the joy of the surprise of some unexpected harmony. With the difficulties that we Italians – I in particular – know how to inflict on those who respect us most, Daniel has undertaken at least a couple of projects with me and my tiny academic hive. This book is the fulfillment of one of these. Hurrah! I thank him for his patience, but above all for the opportunity he gave us to see gathered in this volume, which honors our series, so many extraordinary testimonies to his relevance as a designer and a man of culture and of our, common, stubborn intuitions about the city and its destiny. As responsible for this series, together with him I deeply thank all those who have participated, with their thoughts, their experience as designers and scholars in the success – sure, it will be a success! – of this book. Which is only a stage in a never-ending research. Appendix Never-ending research, as is our conversation. Daniel, who embraced Rome with almost the same trust that Saverio Muratori had in the messages hidden in the historical layers of the fatal city, at times seems more a pupil than I of that extraordinary and dramatic Italian professor. He too – like my ancient adverse-teacher – looks at the human habitat through the eyes of an entomologist who wants to save the Apes Melliferae from an increasingly recurrent disruptive syndrome – let’s put the CCD syndrome [Colony Collapse Disorder] well known in America: flight of active individuals – where to? – abandonment of the orderly social structure of a wonderfully integrated habitat, loss of meaning and function of the spaces and structures of the industrious city. And in his work as an architect he is like the attentive beekeeper who tries to bring the bees back to the hive, society to its original integration by wisely building apiaries that are rich in articulated spaces for the natural, renewed development of balanced and productive life which is inscribed in the destiny of our animal species. I, who, as an Italian of the Roman school, can but be with him, however empowered I feel to reflect more on the behavioral latitude of our species by asking myself if our destiny is really splendidly restricted like that of the very rich species of Apes Melliferae or rather includes instead, the multitude – albeit limited – of behaviors of the numerous winged hymenoptera – from honey bees to the many species of solitary and omnivorous wasps (Ammophila Sabulosa, to name one) in a single, innate greater complexity. And in this latitude of innate behaviors, my thoughts, my feelings, my consciousness, my intuitions being however intrinsic expressions of my destiny – which is that of a certainly complex species like the human – why not give credit to my perceptions to establish what corresponds to my innate aspirations which, however, cannot be outside those established by the original characteristics of my species? It is evening in Gainesville, Florida, sunset is well advanced. My very kind escort tells me to wait for her there, in the long flowerbed that serves as a traffic divider, as she goes to retrieve the car left in a parking lot further away. I thank her. The flowerbed is lens-shaped, green, but with low plants. Two benches in the center. Wide streets curve around where rare cars pass. I know, it’s already dinner time here in America. The city – which city? – is all around me, rarefied, invisible. I glimpse the roofs of some isolated house. The homes of men are sheltered from the gaze like the lairs of solitary wasps, which love to reside next to flowered areas. And perhaps in some of those houses, in a closet, a rifle hangs, like the sting of a wasp, ready for anything, were it really necessary. I sit on one of the benches in the flowerbed, facing the sun in the silence made more evident by the soft noise of American cars, which rush away from time to time. Would this moment never end. I know the evening will be beautiful. The splendid specimen of Ammophila Sabulosa (red-banded sand wasp) that hosts me in Gainesville will return by car and accompany me to its nest among the plants. It will be an evening of peace and conversation in the enjoyment of isolation lived in the fullness of the family unit and selective choice of friendships. Is this the fruit of the CCD disruption? Or maybe this is also an innate model and in any case admitted by our destiny as a species? Otherwise why does all this so naturally enchant me too, who am an unarmed individual of my species? At the presentation of Daniel Solomon’s book Love vs Hope at Sapienza, University of Rome, I wished to point out in my speech that Daniel, however, is an architect of the Acropolis. Or better. He is an architect who takes care of and reconstructs the sense and form of the social and architectural acropolis that the America city wants (or would have wanted?) to be. And I added that his teaching, his example, should be extended to other parts of the city of man, those that are not part of any history of architecture – such as the endless quality – less suburbs of the metropolises of every continent and the spontaneous, enormously vast housing concretions which, being desperately self-built, are just as desperately pure – yes extremely pure – expression of the primary ways of building human habitat, though they are just as, and perhaps more, desperately destructive of a relevant part of our species. Today, I add, I would like to invite him to reflect with all of us, on the profound and inevitable adaptation of every human habitat to the new condition that has made our species pasture and herd of every virus, of every present and future pandemic. In the certainty that for him too architecture is a unitary, necessary, multitude of apparent contradictions resolved in the great flow of history. Unità dell’architettura (Italian text) La Avery Library della Columbia University, NYC, è troppo fredda per chi viene da Roma. “Air conditioning, while it makes us confortable anywhere – ha scritto Daniel Solomon – obliterates the time of day, the weather, the season, and the distinctiveness of the places of the world.” Questa è una delle poche affermazioni di Daniel con le quali sono d’accordo soltanto a metà. L’aria condizionata negli States ti ricorda sempre la distinctiveness americana a causa di quei cinque, sei o persino dieci gradi centigradi sotto il benessere umano cui il termostato viene ostinatamente tenuto ovunque sventoli la bandiera a Stelle e a Strisce, obbligandoti a sentirti unconfortable anywhere, da Chicago a Miami, dalle Hawaii a Portorico, passando per San Francisco e New York, appunto. Ma la Avery Library è uno dei luoghi dove amo di più restare a lungo senza uno scopo preciso muovendomi tra i filari dei suoi scaffali per vendemmiare lentamente libro dopo libro, con l’apparente volubilità con la quale, in Cina, le raccoglitrici – pantaloni larghi e gran cappello parasole – camminano tra i filari di Camellia Sinensis raccogliendo qua e là preziose foglioline del primissimo tè, lasciandole subito cadere – quasi monete d’oro – nel sacchetto che pende dalla loro cintura. Concluso il mio piccolo raccolto di libri, amo allora scendere a sfogliarli nella penombra del piano più basso della Library dove fa ancora più freddo, ma più assoluta è la pace. Scelgo il mio posto in fondo alla sala, guardando l’ingresso. È una scelta pratica; sulla sinistra s’apre la porta di un piccolo laboratorio fotografico dove puoi riprodurre con la fotocamera – oggi con il telefono mobile – le pagine più preziose del tuo raccolto. A destra, più vicino all’ingresso, siede la Signora Librarian, gentilissima, la cui amabilità tenta di vestire di buona stoffa inglese una rigida severità americana. Era luglio quella volta e la signora indossava un vestitino estivo. A me non bastava aver indossato uno sweater sotto la giacca e averne allacciato tutti i bottoni. Avevo freddo. Ma dovevo resistere, convinto allora come ora che questa sia certamente la prova cui ti devi sottoporre negli States, per dimostrare d’esser degno del loro standard di civiltà. Nella mia svagata vendemmia libraria ero stato accompagnato da una giovane allieva italiana, che aveva rifinito alla Columbia University la sua tesi del Dottorato de La Sapienza. Mentre mi accomodavo nella gelida sala di lettura, ella s’era attardata ancora un po’ tra gli scaffali a spigolare qualche altro testo; mi raggiunse nella sala di lettura poco dopo, veloce, in punta di piedi. Con un sorriso quasi trionfante aggiunse alla mia piccola pila di libri un libro di sua scelta dal titolo “Global City Blues”. Bel titolo, sussurrai sottovoce mentre notavo il nome dell’autore: Daniel Solomon, a me ancora sconosciuto. Pensai che la giovane PhD avesse voluto offrire quel libro alla mia attenzione in virtù della parola Blues. Ella conosceva bene la mia passione per le dodici battute, le blue notes e tutto il resto, che coltivavo da quando sessant’anni prima – ero davvero bambino – la Quinta Armata del generale Clark s’era presentata a Roma liberandoci dai resti della Quattordicesima armata del Generale von Mackensen. Con gli americani, di colpo era arrivato a noi di Roma il Mondo Nuovo con i suoi modi spicciativi, con la sua inaudita modernità. La sua musica e, con essa, il Blues. Il Blues vero intendo, non solo quello che sosteneva i boogies di Glenn Miller, ma il Blues profondo ed ingenuo che i soldati neri strimpellavano su chitarre male accordate appoggiati alle loro Jeep ferme in strada, in attesa che i graduati bianchi uscissero dal Comando e ordinassero di portarli altrove. E mia madre, musicista studiosa di Folkmusic, alla mia precoce fissazione per quel ripetitivo giro di note aveva risposto insegnandomene con precisione la scala ed i più classici riff. Ma sbagliavo in pieno; il libro di Daniel Solomon non era stato scelto per compiacere la mia passione per il Blues. Questo libro parla di Wu, mi disse a voce bassissima la giovane allieva: parla del professor Wu Lianyong. Il professor Wu Liangyong in quei primi anni del nuovo secolo era già il grande vecchio dell’architettura Cinese moderna, scuola di Pechino. Aveva già superato gli ottanta anni. Ne percepivi l’immanente presenza appena un collega cinese, pronunciandone il nome per introdurti alla storia della facoltà di architettura della Tsinghua University, istintivamente volgeva gli occhi verso la cima della grande scala che porta ai piani superiori dall’atrio di quella famosa scuola dove si fronteggiano le riproduzioni di un Ordine greco e dell’Ordine cinese. Il professore-fondatore, dunque, dimorava ancora nel suo monte Olimpo, così prossimo a noi mortali. A quei tempi nessuno in Italia conosceva il professore e architetto Wu Liangyong. Non una storia dell’architettura contemporanea riportava il suo nome o aveva pubblicato opere sue. Non un articolo di rivista era mai stato dedicato a lui. In verità l’architettura moderna cinese e la città cinese contemporanea erano sostanzialmente ignorate anche dai nostri storici più aggiornati. L’eleganza astratta di Ieoh Ming Pei, consonante tributo alla modernità occidentale, sembrava aver stabilito la via che gli architetti cinesi avrebbero dovuto percorrere per entrare nella storia dell’architettura contemporanea. Una via che sarebbe stata difficile da percorrere con convinzione anche da noi architetti italiani. Mi ero iscritto alla Facoltà di architettura di Roma quasi cinquant’anni prima della scoperta del Blues di Daniel Solomon. Avevo diciotto anni. L’America, gli svettanti grattacieli appresi a bocca aperta nei film di Hollywood, la velocità, la linea delle Studebaker Commander del 1954; questa è la modernità, mi dicevo, l’unica che può far sentire vivi noi giovani. Nei libri di Storia dell’arte Italiana ed Europea del mio Liceo Classico avevo cercato qualcosa che somigliasse a quel vigore primordiale. L’architettura moderna, in quei libri scolastici, era trattata come un’appendice aggiunta al testo per giustificare una nuova edizione. Soltanto un disegno a penna, in bianco e nero di Erich Mendelsohn – i Magazzini Shocken – riprodotto in una piccola immagine , mi sembrò avesse qualcosa di quello slancio vitale. Presi a ridisegnarlo con la mia penna stilografica ed a reinventarlo ogni giorno tralasciando tutto ciò che avevo appreso, negli ultimi tre anni di liceo, da quei ponderosi volumi di storia dell’Arte Italiana ed Europea; entusiasta, ignaro pellegrino sulla strada di Ieoh Ming Pei. Ma, nello stesso periodo, sfogliando un altro ponderoso libro d’arte, scoperto spigolando a tempo perso nella biblioteca di mia madre – appassionata di musica e di teatro – fui attratto delle ricostruzioni prospettiche delle “vedute per angolo” di Ferdinando Galli da Bibbiena (1657-1743). Ah – mi dissi – ecco le segrete leggi fisiche che si celano dietro le spettacolari quinte del teatro classico e barocco, retorico e musicale; ecco cosa induce in noi, ignari spettatori, l’illusione e l’emozione percettiva che ci fa aderire anche sentimentalmente a un luogo, immaginario o reale che esso sia, anche se costruito nella ripetizione dei più classici e “vecchi” motivi architettonici. “Dunque –mi dicevo – la grande architetture delle vecchie città, dei loro monumenti polverosi, così lontana dalle vibrazioni vitali della modernità è soltanto il vestito di cerimonia di un congegno intellettuale modernissimo, fatto di geometrie assolute e variabili, di rapporti matematici a me ancora incomprensibili, di fughe verso diversi infiniti – a destra a sinistra, in alto, perfino in basso – che si dipartono dagli oggetti che sembrano invece, stolidamente tradizionali, quasi stantii nella loro secolare ripetizione di simboli antichissimi...”. “No, ti prego, fatti consigliare da tuo padre su come si costruisce una casa in questo paese così bello” Così si rivolgeva mia madre al figlio del contadino che ci aveva ospitato dieci anni prima ad Arquata del Tronto, nella prima estate del 1943 – la guerra era ormai in Italia – mentre trascorrevamo un sembiante di villeggiatura che era, invece, una fuga in campagna, dove qualcosa da mangiare si poteva, forse, trovare. E dove, soprattutto, non c’era pericolo di bombardamenti. Arquata è un paese dominato dalla rovina di un castello medievale e affacciato sulla valle ancora angusta del fiume Tronto che dai monti Sibillini dell’Appennino si precipita verso il mare Adriatico. Il ragazzo stava iniziando a costruire la casa per il suo prossimo matrimonio; in fretta. Era giovanissimo, voleva sposarsi prima di partire per il fronte. Con un gruppo di amici aveva iniziato a tracciare le fondazioni. Non so da cosa mia madre desumesse l’imperizia del giovane. Forse i materiali scelti per l’occasione – roba di modernità autarchica e di poco prezzo – forse la forma della pianta, forse il fatto che la costruisse isolata nel prato davanti a quella del genitore. Non so. Ma glielo chiesi. Mi disse qualcosa sulla modernità che fa perdere le regole dell’abitare; dunque del costruire. Non capii. Se ne accorse. Da quel giorno, nelle passeggiate attraverso il paese o nelle brevi visite nelle case per comprare un po’ di latte o di pane appena estratto dal forno, non mancò mai di farmi notare i materiali di cui erano costruite le case, l’ordine spontaneo, ma costante, delle porte e delle finestre, le varianti, pochissime, delle scale esterne e interne e la forma della cucine attorno a cui tutta la casa disponeva le altre stanze. Quando andavamo nei campi a monte del paese mi indicava il profilo degli insediamenti lontani, il colore di quei grumi di murature antiche così simile agli altri colori del paesaggio. E infine, naturalmente, mi parlava della grande Sibilla che un tempo – ancora prima dei romani antichi! – abitava sul monte più alto e – chissà – forse ancora ci abitava se le ragazze di una valle accanto alla nostra una volta l’anno si uniscono in una antica danza per onorarla. Mio cugino Giuseppe aveva 10 anni più di me. Nato a Catania, in Sicilia, si era laureato in Ingegneria al Politecnico di Torino; divenne uno dei primissimi ingegneri nucleari del mio Paese. Mentre frequentava il suo Master of Science in Ingegneria Nucleare a Latina, non lontano dalla Capitale, in un corso tenuto un po’ in segreto dagli USA, spesso era ospite a casa mia, a Roma. Con lui parlai del mio futuro con maggiore libertà che con i miei genitori. Ero ancora incerto: Medicina? Fisica? ... Architettura? Gli parlai dell’Architettura con passione, ma esprimendogli il mio grande disorientamento. No, non volevo scegliere di essere disorientato per la vita. Oh, sì, l’architettura era bellissima, ma mi induceva pulsioni contrastanti, confusione, come amare tre ragazze diverse, contemporaneamente... Il cugino Giuseppe vide i miei ingenui disegni modernisti, mi lasciò parlare di Bibbiena e dei paesi antichi, dei miei interrogativi su “l’arte di abitare” come diceva mia madre. Sulla modernità e la tradizione (a quei tempi dicevo “l’architettura vecchia”). Poi gli parlavo della Fisica, di cui non sapevo nulla, ma mi pareva emanare la certezza della ricerca della verità; poi della Medicina, che cercava la verità nell’uomo per aiutarlo a vivere, a sopravvivere. Due mestieri che mi apparivano allora senza ombre, anzi perfino nobilitati da uno scopo umanitario: il progresso della scienza, la cura degli altri. Quali delle due strade intraprendere: Fisica o Medicina? Lo chiedevo a un novello scienziato della più moderna tra le Scienze di allora. Devi inscriverti ad Architettura, mi rispose. Adesso sei come uno scaffale di biblioteca dove hai cominciato a mettere, l’uno accanto a l’altro, libri che parlano della città e degli uomini che la vivono, libri che paiono in insanabile contrasto fra loro, la cui sola vista ti crea disorientamento. Ma è proprio trasformando noi stessi in una biblioteca in cui tutto – tutte le idee intendeva – può comunicare con tutto – con tutte le idee intendeva –, anche con l’opposto da sé, si può sperare di contribuire al progresso della scienza, della ... filosofia... delle città... dell’architettura. Mamma mia. Parlava certamente con parole apprese nel Master of Science più esclusivo d’Italia. Dopo ancora alcuni giorni di discussione gli comunicai che avevo deciso: mi inscriverò ad Architettura. “Allora ricorda”, mi disse: “non seguire l’ultima moda. Tieniti un passo di lato, metti tra te e la moda tutta la tua libreria interiore”. Non capii bene, ma mi piacque molto. Quella sera, al termine della cena, alla presenza del cugino Giuseppe – mio sponsor – comunicai ai miei genitori la mia decisione. “Oddio!” disse mio padre, professore di materie umanistiche proveniente da una famiglia di professori di materie umanistiche o scientifiche. E guardò mia madre che non ricambiò il suo sguardo allarmato, ma sorrise mentre era intenta a sbucciare una mela con forchetta e coltello. Forchetta e coltello non erano contemplati dallo stile con il quale i professori di architettura, ai miei tempi, trattavano le matricole e, in generale, gli studenti del primo biennio. Sottomissione al lavoro senza tregua, apprendimento della architettura attraverso la ricostruzione, dal vero o dai documenti, di tutti gli stili del passato e, soprattutto, dei grandi nodi architettonici di ogni stile. Inflessibile affermazione del mestiere dell’Architetto come quello di un durissimo artigianato, professato usando con padronanza ogni arnese antico. Di arnesi moderni non ve ne erano ancora. Comunque non ve ne erano nella nostra scuola. Nel triennio superiore, poi, il tono di molti professori era quello dell’autorità militare che, nel caso dei più cólti fra loro, assumeva il tono – io credo – delle università medievali; assolutezza teologica degli assunti e, parallelamente, eversione erasmiana degli studenti trascuratamente tollerata dai docenti, per poi essere repressa, dagli stessi docenti, pubblicamente, se ne avevano il tempo e la voglia. La modernità, la modernità senza aggettivi dove era? Serpeggiava soltanto tra noi studenti ed era divenuta sinonimo di libertà. Ahi! Nonostante tutto, durante quel tirocinio autoritario in cui pochissimi docenti, per lo più giovani, sembravano voler ambiguamente aprire un dialogo con noi giovani modernisti-per-età, imparai molto. Imparai soprattutto che le mie radicali contraddizioni iniziali tra la modernità primordiale, il miraggio di metastoriche regole compositive e l’incanto dell’abitare naturale – che pareva cancellare in radice la necessità dell’esistenza dell’architetto – in una scuola italiana d’architettura non avrebbero trovato la risposta netta che attendevo a favore dell’una o dell’altra. Specie nella scuola di Roma, dove quelle contraddizioni, assieme a tante altre che all’inizio neanche sospettavo, parevano risolversi coesistendo tutte in una unitaria, necessaria moltitudine nel grande flusso della storia. La mia classe, come le due o tre precedenti, al quarto anno di corso si imbatté in un professore che voleva essere decisivo. Decisivo e oppositivo. Oppositivo non soltanto rispetto ai metodi didattici della facoltà, autoritari ma, in fondo, lassi; oppositivo soprattutto e più precisamente rispetto all’unitaria moltitudine di contraddizioni che, malgrado le nostre aspirazioni moderniste, avevamo cominciato a riconoscere nell’identità dell’architettura. Quel professore era Saverio Muratori, titolare della cattedra di Composizione architettonica da poco; dal 1955. Modernità, tradizione, linguaggio, tecnologia, storia – il suo scorrere, intendo, che rende relativa ogni verità – tutto nel suo corso era usato come un’attrezzeria indispensabile alla ricerca, ma un’attrezzeria “ancillare”, cioè posta fuori dalla scena che essa contribuiva a costruire, o meglio: fuori dal quadro degli scopi della sua ricerca. La quale voleva essere una ricerca scientifica sulle leggi del costruire l’abitazione dell’uomo sul pianeta: negli smisurati e diversi spazi naturali e climatici, nelle diversamente opportunistiche colonizzazioni agricole, nei villaggi di diversa materialità e cultura e – infine e per cominciare – nella città. A prescindere dal tempo. Dunque dalla storia. E la città di Roma, la città per eccellenza, da lui che proveniva da una tradizione familiare padana – ricordiamo i Galli? E i Longobardi? E i liberi Comuni? – era stata abbracciata con passione e prescelta come il campo di ricerca privilegiato dal quale, con la maggiore chiarezza possibile, attraverso i più intatti e numerosi esempi della più alta forma del costruire, si sarebbero potute estrarre le leggi che presiedono all’agire dell’uomo nel dare forma – meglio: nel dare linguaggio al proprio da-sein, al proprio esserci, sul pianeta. Era come se Roma, finalmente e in modo letteralmente magistrale, potesse fornire materia suprema di indagine per la sua ricerca – iniziata anni prima in una Roma di confine, bizantina e medievale: Venezia – e, contemporaneamente, rappresentasse la prova che sì, davvero le grammatiche e i principi costruttivi di ogni cultura possedessero una struttura profonda comune e comuni principi formativi. Anni più tardi, noi giovani modernisti avremmo potuto riconoscere nella ricerca di Saverio Muratori gli stessi motivi ispiratori della Grammatica generativa di Noam Chomsky. Ma a quell’epoca – proprio alla fine degli anni Cinquanta – di Chomsky non si sapeva ancora nulla in Italia anche se egli aveva appena scritto il suo primo saggio importante, Syntactic Structures, nel 1957. Oh, sì; quando il pensiero di Chomsky raggiunse anche noi ancora giovani architetti italiani e ci interessò più per le posizioni politiche che per i raggiungimenti scientifici, davvero mi sembrò di aver tra le mani la prova di quel che avevamo intuito della ricerca di Saverio Muratori; il suo essere una ricerca simile a quella di un entomologo che indaghi le modalità innate di costruire il proprio habitat degli imenotteri alati, prendiamo le api, nelle loro varianti di specie e di ambiente – cioè di cultura e di contesto, volendo tornare al caso umano. Infatti: non era forse Chomsky ad aver apertamente stabilito che il linguaggio, cioè la più alta espressione di identità di ognuna delle civiltà umane disperse nella storia e nella geografia altro non fosse che una variante adattiva, contingente, dunque storica, della struttura linguistica innata e permanente di una specie animale, la nostra? E in fondo Saverio Muratori, non cercava di dimostrare che ciò che chiamiamo architettura in tutte le sue varianti linguistiche, in tutta la sua ricchezza tematica e formale, ambientale, non sia mai frutto di decisioni innovative, ma unicamente di scelte obbligate in un repertorio ancorché vastissimo comunque limitato perché dato come innato e ammesso come possibile dalla nostra stessa natura? L’architettura non come atto creativo, non come sempre rinnovata decisione del pensiero, ma come destino. Ahi! Di questo, con altre parole, discutevamo tra noi dopo ogni lezione del professor Muratori. E noi giovani modernisti, che per convivere con l’idea di architettura come unitaria moltitudine di contraddizioni avevamo trasfigurato la modernità in libertà, non volemmo arrenderci all’idea dell’architettura come destino preordinato. Dopo aver frequentato con ardimentosa stizza le lezioni del professor Muratori e aver imparato a perfezione – e per dispetto – le tabelle classificatorie della nascita e dello sviluppo dei tipi abitativi e delle aggregazioni morfologiche dell’habitat umano ed aver infine progettato moduli spaziali a-funzionali – quasi cavità originarie a disposizione di ogni necessità primordiale – tipi abitativi elementari, aggregazioni preordinate di abitazioni e piccoli servizi, luoghi di lavoro modulari e – ecco ci siamo! si chiude il cerchio – grandi invasi monumentali che dal Pantheon e dalle grandi caverne carsiche mutuavano il loro spazio, ci ribellammo. Buttammo all’aria sia il corso che il predominio del professor Muratori nella scuola. Ma la consapevolezza dell’architettura come destino di specie scivolò nel fondo della nostra coscienza di nascenti architetti, senza dissolversi. Senza dirlo a noi stessi, sapevamo bene che nella antica dialettica tra libertà e destino la libertà potrebbe davvero vincere se il fato si piegasse alla volontà umana. Ma, come ci insegnano gli antichi, il fato non si piega neanche alla volontà degli dei. Così, la nostra volontà di progettisti che, inseguendo il volo di chi eleggiamo a “stars” dell’architettura, vorrebbe avere sempre la forza rivoluzionaria di un drammatico travolgimento d’amore per realizzare pienamente, nella libertà dell’invenzione, la nostra identità di architetti, nella realtà è pur sempre una volontà di specie che permane nello spazio del suo destino. Per questo l’esperienza non senza drammi che avemmo nel corso del professor Muratori, invece che sconfiggere l’idea dell’architettura come unitaria, necessaria, moltitudine di contraddizioni risolte nel grande flusso della storia, la perfezionò. Nello spazio del destino di specie le contraddizioni sono soltanto apparenti, essendo, tutte, soltanto quelle contemplabili dalla nostra originaria natura. E mi parve che la difficoltà di essere “moderni” che traspare dalla recente storia dell’architettura italiana non fosse sintomo di una arretratezza, ma di una consapevole – o il più delle volte inconsapevole – resistenza rispetto all’illusione di considerare la storia come sequenza di atti di rottura, negazione – condanna – superamento di ogni recente passato, quello da cui ogni generazione proviene. Così, nella mia prima giovinezza accademica lessi e rilessi in questo quadro la storia recente dell’architettura italiana tempestandola di domande per avere conferme: forse gli italiani tra le due guerre, non fecero del Futurismo – così verbale e gestuale e teatrale e commovente per il destino di Sant’Elia – lo schermo dietro il quale difendersi dal disperato funzionalismo germanico che rifiutava ormai – dopo la sconfitta nella Grande Guerra – ogni rapporto con la Storia? E in quei decenni, gli architetti italiani non usarono tutti i possibili idiomi della loro cultura – fatta di profonde e antiche diversità – per ristabilire comunque la continuità con le ricerche d’architettura interrotte dalla prima guerra mondiale, tra le quali, appunto, stava lo stesso Futurismo? E Terragni – e Libera con lui – non aveva voluto intendere la modernità essenzialmente come decisiva esperienza formale nella storia –sempre, dunque, tenendosi libero di far scorrere la propria matita e il proprio pensiero tra tutte le forme simboliche del classicismo – da Michelangelo al Novecento – e della modernità – dal Futurismo, all’Espressionismo, alla costruzione e decostruzione a-funzionale dello spazio fino alla sublime interpretazione della città moderna come pura forma simbolica sintetizzata nel misterioso grumo architettonico della palazzina Frigerio? E quanto volte per sostenere la loro posizione rispetto al mondo moderno gli italiani non cercarono ogni sostegno “esterno” alle loro convinzioni linguistiche? Nel secondo dopoguerra, infatti, negli anni della mia prima formazione, la cultura architettonica ufficiale italiana non continuò forse nel suo sforzo di evitare lo “stile internazionale” – ormai vincente – scantonando nel neo-realismo, come se ciò fosse imposto davvero dalle particolari condizioni di arretratezza delle masse popolari della Roma moderna e del nostro Mezzogiorno? e la ripresa linguistica e culturale Neo-Liberty, non fu attribuita forse alle esigenze di stabilità e identità della borghesia industriale del Nord Ovest? E l’immagine iper-castellana della Torre Velasca non ravvivò dunque la tradizione medievista della Scuola d’architettura dell’ottocentesco Regno del Lombardo-Veneto? E il linguaggio “reazionario” di Aldo Rossi non affermò, quindi, l’attualità del neoclassicismo lombardo che tutti noi italiani avevamo appreso, ancora scolari, nelle settecentesche poesie di Giuseppe Parini? E infine: l’esperienza di Carlo Scarpa – bizantina nella preziosità dell’oro, del vetro e delle materie umili rese preziose dal suo disegno – non usò forse il polilinguismo di Frank Lloyd Wright come passaporto per essere accolta nel reame della modernità senza passare per la dogana dello “stile internazionale” o peggio ancora per quella del più rigido tardo funzionalismo centro-europeo? Per ampliare la mia politeistica palestra di questioni, (continua)